2020
DOI: 10.1080/14786419.2020.1819270
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic activities of compound GL-1, isolated from Ganoderma lucidum

Abstract: In this study, the estrogenic effect of GL-1, a component of the Ganoderma lucidum, was studied, and the possible mechanism was discussed preliminarily. The binding ability of GL-1 to estrogen receptor was calculated by computer-aided simulation. The effects of GL-1 on the proliferation of estrogen sensitive estrogen receptor (ER) (+) MCF-7 cells and estrogen insensitive ER (-) MDA-MB-231 cells were detected by MTT method. The effects of GL-1 on the proliferation of estrogen-induced MCF-7 cells, and the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It has been shown that estrogen can regulate the expression of ACE-2 receptors [ 5 ]. Although a few known herbal medicines such as extracts of Ganoderma lucidum , Perilla frutescens , and Mentha haplocalyx have been shown to be effective against SARS-CoV-2 infection [ 33 ], only Ganoderma lucidum has shown effect on estrogen modulation [ 34 ]. Since Cipa appears to have ESR1 modulatory effects [ 10 ], and has been shown to have antiviral potential [ 8 ], we hypothesized it may have inhibitory effect on the novel coronavirus.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that estrogen can regulate the expression of ACE-2 receptors [ 5 ]. Although a few known herbal medicines such as extracts of Ganoderma lucidum , Perilla frutescens , and Mentha haplocalyx have been shown to be effective against SARS-CoV-2 infection [ 33 ], only Ganoderma lucidum has shown effect on estrogen modulation [ 34 ]. Since Cipa appears to have ESR1 modulatory effects [ 10 ], and has been shown to have antiviral potential [ 8 ], we hypothesized it may have inhibitory effect on the novel coronavirus.…”
Section: Discussionmentioning
confidence: 99%